Carrot and Stick? Impact of a Low-Stakes School Accountability Program on Student Achievement - Seokjin Woo; Soohyung Lee; Kyunghee Kim (Institute for the Study of Labor (IZA), 2015)
A key concern in the design of education policies relates to the structure of incentives in accountability systems. This paper examines a school accountability program that provides financial support to low-performing schools but has no direct punishment scheme for recipients who do not exhibit improvement. Although the program does not include high-stakes consequences, our estimates indicate that the program reduced the share of underperforming students by 18 percent. This paper's results suggest that to improve student achievement, a school accountability program does not need to set high-stakes consequences that potentially induce unwanted strategic behaviors on the part of school workers.
Keywords: C5; I2; 330; school accountability; student achievement; school performance; fuzzy regression discontinuity design